Sustainable development with green economy in the Río Fucha basin - Alarcón Romero, Jessica Alexandra; Morales Ospina, Alberto; Alarcón Romero, Jessica Alexandra; Morales Ospina, Alberto (Corporación Universitaria Americana, 2021)
The Fucha river through the city of Bogotá in thedepartment of Cundinamarca, which originates in theEl Delirio forest reserve in the Cruz Verde moor andempties into the Bogotá river. In its first two kilometersthe channel does not It is contaminated, the rest has aregular and poor state of conservation, since for decadesit has been used as a sewer receiving waste and sewage.The challenge of the intervention for the recovery ofthe Fucha river was to give it a reinterpretation of theinteraction between people and the environment as apublic space, integrating diverse informal recyclers intoformal solid waste management systems presentinga series of challenges and opportunities when carriedout successfully, bearing in mind that their work canimprove performance of the system and environmentalsustainability while maintaining and even progressingin the development of living conditions p For the peoplearound him and the informal recyclers, it also helps toimplement job opportunities for the recyclers, there aredifferent methods to implement different activities whichlink the different elements of society.